2022
DOI: 10.1007/s00521-022-07895-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep feature selection using local search embedded social ski-driver optimization algorithm for breast cancer detection in mammograms

Abstract: Breast cancer has become a common malignancy in women. However, early detection and identification of this disease can save many lives. As computer-aided detection helps radiologists in detecting abnormalities efficiently, researchers across the world are striving to develop reliable models to deal with. One of the common approaches to identifying breast cancer is through breast mammograms. However, the identification of malignant breasts from mass lesions is a challenging research problem. In the current work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…GoogleNet (Inception) developed the concept of inception modules, which use parallel convolutional operations utilizing various kernel sizes for capturing multi-scale features efficiently. TL -Inception (Mahmood et al, 2021) Malathi and Latha, 2023;Sakthivel et al, 2022b;Samee et al, 2022b,a;Singh et al, 2023;Ahmad et al, 2023;Arora et al, 2020;Hekal et al, 2021) TL -VGG Net (Mahmood et al, 2021), (Jones et al, 2023;Pramanik et al, 2023;Sajid et al, 2023;Salama et al, 2020;Samee et al, 2022b,a;Yu et al, 2023a;Arora et al, 2020;Boudouh and Bouakkaz, 2023c;Chakravarthy et al, 2023b;Nemade et al, 2023a;Rani et al, 2023) TL -DenseNet (Mahmood et al, 2021), (Kumbhare et al, 2023;Zhang et al, 2020;Boudouh and Bouakkaz, 2023c;Chakravarthy et al, 2023b;Saber et al, 2023;Malibari et al, 2022) The Inception architecture has gone through several iterations. Inception-v2, also known as BN-Inception, added batch normalization to accelerate training.…”
Section: Rq2: What Are the Unique Challenges And Considerations In Ap...mentioning
confidence: 99%
See 1 more Smart Citation
“…GoogleNet (Inception) developed the concept of inception modules, which use parallel convolutional operations utilizing various kernel sizes for capturing multi-scale features efficiently. TL -Inception (Mahmood et al, 2021) Malathi and Latha, 2023;Sakthivel et al, 2022b;Samee et al, 2022b,a;Singh et al, 2023;Ahmad et al, 2023;Arora et al, 2020;Hekal et al, 2021) TL -VGG Net (Mahmood et al, 2021), (Jones et al, 2023;Pramanik et al, 2023;Sajid et al, 2023;Salama et al, 2020;Samee et al, 2022b,a;Yu et al, 2023a;Arora et al, 2020;Boudouh and Bouakkaz, 2023c;Chakravarthy et al, 2023b;Nemade et al, 2023a;Rani et al, 2023) TL -DenseNet (Mahmood et al, 2021), (Kumbhare et al, 2023;Zhang et al, 2020;Boudouh and Bouakkaz, 2023c;Chakravarthy et al, 2023b;Saber et al, 2023;Malibari et al, 2022) The Inception architecture has gone through several iterations. Inception-v2, also known as BN-Inception, added batch normalization to accelerate training.…”
Section: Rq2: What Are the Unique Challenges And Considerations In Ap...mentioning
confidence: 99%
“…K-nearest Neighbor (KNN) (Gnanasekaran et al, 2020), (Khanna et al, 2022;Pramanik et al, 2023;Jabeen et al, 2023;Malathi and Latha, 2023;Mokni and Haoues, 2022;Qu et al, 2022;Razali et al, 2023b,a;Sajid et al, 2023;Samee et al, 2022b,a;Sannasi Chakravarthy and Rajaguru, 2021;Zahoor et al, 2022) KNN classifies a data point according to the majority group of its k-nearest neighbors.…”
Section: Continuation Ofmentioning
confidence: 99%
“…affected women [17][18][19][20]. Among these efforts, deep learning-based CAD systems have shown great promise to address this challenge.…”
Section: Plos Onementioning
confidence: 99%
“…The research found a number of ideal features and had an accuracy rate of 83.74%. Pramanik et al [111] explored the use of deep features extracted from breast mammograms to predict breast mass. The study identified 25% of the predictive features and achieved an accuracy of 96.07%.…”
Section: Data Sourcesmentioning
confidence: 99%